(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1989)
Five lecture summaries: Elginhaugh: A Roman fort and its environs The greater medieval burgh kirks William Elphinstone, bishop and founder of the University of Aberdeen Scottish graveyards A hard-won wilderness: man and environment on Foula, Shetland and Western Faroe